A trinomial is a polynomial that has three terms.
Let the unknown trinomial be represented by A
Thus, the difference between the two trinomials as stated in the question will be represented mathematically as;
![\begin{gathered} A-(3x^2-2x+7)=5x^2+11x-16 \\ \text{Making A the subject of the formula, we have} \\ A=(5x^2+11x-16)+(3x^2-2x+7) \\ \operatorname{Re}\text{arranging and collecting the like terms, we have;} \\ A=5x^2+3x^2+11x-2x-16+7 \\ A=8x^2+9x-9 \end{gathered}]()
Therefore, the expression of the other trinomial is;
![A=8x^2+9x-9](https://img.qammunity.org/2023/formulas/mathematics/college/c3pnwcuojhd14lsslxhx9xv71259qxmrl6.png)
The correct answer is option C.